A COMPARISON OF THE FLEXURE BEHAVIOR OF NORMAL CONCRETE BEAM COMPILED BY GRAVEL AND CRUSHED STONE - Samuel Layang; Wiratno (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2013)
This research purposed fordiscoverfigure of concrete beam flexure failure. Its concrete beams researched are composed by coarse grain aggregate of gravel and crushed stone. This research was conducted by 10 (ten) concrete cylinders (Ã˜15 cm x 30 cm) and 5 (five) concrete beams(60 cm x 15 cm x 15 cm). Normal concrete mix design is calculated by SNI 03-2834-2000 method.The result of this research has showed if average compressive strength of crushed stone concrete is 11.511 MPa and 12.449 MPa for gravel stoneconcrete. The average beam bending capacity of crushed stone concrete is 1.002kNm and 1.054 kNm for gravel stone concrete. The crack pattern of all tested beam considered similar. The crack occur was done in the middle of beam, moving by bottom to top which analogous to increasing load to the center of load. The failure of all tested beam are considered as flexure failure.